Analysis of Park and Ride Location Determination in Urban Areas Using Analytical Hierarchy Process (AHP) - Casuya Casuya; Muhamad Faisal; Muchammad Arif Saifutdin; Mira Lestira Hariani; Ohan Farhan (Riviera Publishing, 2025)
The rapid growth of private vehicles in urban areas has caused various problems such as traffic congestion, increased air pollution, excessive fuel consumption, and decreased quality of life. The urgency of this research lies in the need for strategic solutions to reduce the use of private vehicles in the city center, one of which is through the construction of Park and Ride (PnR) facilities integrated with public transportation. The purpose of this research is to determine the strategic location of PnR facilities in Cirebon City to support a more sustainable urban transportation system. This research uses the Analytical Hierarchy Process (AHP) method involving ten main criteria, including parking lot capacity, supporting facilities, ease of access, transportation integration, intermodal connectivity, and development costs. Data was obtained through expert surveys and secondary data from relevant agencies. The results showed that the alun-alun kejaksan area is the most optimal location for the development of PnR facilities, followed by Kejaksan Station, Prujakan Station, and Harjamukti Terminal. This location is superior in terms of accessibility, land capacity, transportation mode integration, and proximity to community activity centers. These findings are expected to be a reference in planning and policy making for the development of urban transportation systems in Cirebon City.